Thatcher's diplomacy the revival of British foreign policy - Sharp, Paul 1953- (Contemporary history in context series, 1997)
British foreign policy under Margaret Thatcher has been completely misunderstood by friends and foes alike. The former praise her strong personality, her willingness to stick up for Britain in Europe, and the loyal support she provided the Americans in the last decisive flare up of their rivalry with the USSR. Her foes condemn her for precisely the same reasons. Both agree, however, it is not for her contribution to foreign policy that she will be remembered, as she remained stuck in the categories of the Cold War and earlier. Sharp takes issue with this reading and by assessing her whole international record from 1979 to 1990, demonstrates how Thatcher emerged as the first authentic statesman of the post-Cold War. It was Thatcher who realized that the fading of the Cold War provided new opportunities for independent and assertive action by the European great powers, and it was Thatcher who recognized the revived importance of nationalism, not just as a constraint upon international cooperation, but as the positive cornerstone on which all such cooperation must still be built.